AMOUNTS OF SALIVARY TOTAL PROTEIN BEFORE AND AFTER ORTHODONTIC TOOTH MOVEMENT - v Arash, (Babol University of Medical Sciences, 2008)
BACKGROUND AND OBJECTIVE: Mechanical stress alters the secretory proteins concentration at the local level in bone and the oral cavity. Recognition of these proteins and their roles in teeth movement or tissue destruction diagnosis is very important. The aim of this study was to evaluate the changes of total protein concentration in whole saliva (WS) before and after orthodontic tooth movement.METHODS: This experimental study was done on 40 adolescent and young patients who were in need of orthodontic treatment for both jaws. Samples of W.S. were collected once before the placement of orthodontic separators, and 1 day and 1 week after the placement of orthodontic separators. Total protein concentration was measured by spectrophotometric method.FINDINGS: Total protein concentration before the placement of orthodontic separators, 1 day and 1 week after were 127.3, 135.1, 131.6 (mg/dl). Total protein concentration elevated after initial tooth movement (one day after the placement of orthodontic separators) and then, tended to the pretreatment levels at the 7th day, but it didn’t exactly return to it (p<0.001(. It was not found a correlation between total protein alterations and sex. CONCLUSION: According to the results of this study, the application of force and the placement of separators increase the total protein in whole saliva. Therefore it may be possible that some of the new released protein index due to forcing is recognizable with analysis of saliva and its relationship with the effect of orthodontic treatment can be studied.